1995
DOI: 10.1111/j.1399-3054.1995.tb05523.x
|View full text |Cite
|
Sign up to set email alerts
|

Relations between cytokinin level, bud development and apical control in Norway spruce, Picea abies

Abstract: In conifers such as Norway spruce, the extent of shoot growth is predetermined by the size and number of embryonal organs of the buds laid down the previous year. As it is known that cytokinins have a key role in bud development a possible hypothesis is that the level of cytokinin in the buds during their formation determines their size and complexity. As a first step to test this hypothesis we compared cytokinin levels in buds of different size of annual shoots from 15‐ to 20‐year‐old trees of Picea abies (L.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 27 publications
(23 reference statements)
2
13
0
1
Order By: Relevance
“…This supports previous studies in which cytokinins were shown to regulate bud differentiation and shoot development in Norway spruce (Bollmark et al 1995;Chen et al 1996) and radiata pine (Zhang et al 2001(Zhang et al , 2003. In angiosperms, cytokinin receptors have different affinities for Z-type and iP-type cytokinins (Spíchal et al 2004;Romanov et al 2006).…”
Section: Discussionsupporting
confidence: 88%
“…This supports previous studies in which cytokinins were shown to regulate bud differentiation and shoot development in Norway spruce (Bollmark et al 1995;Chen et al 1996) and radiata pine (Zhang et al 2001(Zhang et al , 2003. In angiosperms, cytokinin receptors have different affinities for Z-type and iP-type cytokinins (Spíchal et al 2004;Romanov et al 2006).…”
Section: Discussionsupporting
confidence: 88%
“…the cytokinin concentration in buds is correlated with their size and position, with terminal buds containing more than subterminal buds (Bollmark et al 1995, Chen et al 1996. Gradients in physiological properties between buds in different positions in the crown, a relatively unexplored phenomenon, may explain why the results seem to differ depending on the kind of buds removed.…”
Section: Discussionmentioning
confidence: 91%
“…The reactions, which surpass the effects of any other debudding studies in conifers known to the authors (Lanner & Connor 1988, Wilson 1992, Wang et al 1997, may be so strong because young trees with relatively few buds were used. Conifer buds are known to contain auxins as well as cytokinins, the concentration of which is rising towards the time of budbreak (Aldén 1971, Qamaruddin et al 1990, Bollmark et al 1995, and removal may have been able to alter considerably the phytohormone balances within the plants. The enhanced growth in length and girth Downloaded by [Australian National University] at 10:57 05 June 2016…”
mentioning
confidence: 99%
“…Grafting studies with the rms4 branching mutant and wildtype plants show that the shoot controls the import of cytokinins from the roots (Beveridge et al 1997). Bollmark et al (1995) have proposed that polarly transported auxin may control bud outgrowth by regulating cytokinin metabolic changes. Auxin might act by controlling the level of active cytokinins (e.g.…”
Section: Discussionmentioning
confidence: 98%